Titanium-Catalyzed Intermolecular Hydroaminoalkylation of Terminal Alkynes - Thye, Hermann; Fornfeist, Felix; Geik, Dennis; Schlüschen, Levi L.; Schmidtmann, Marc; Doye, Sven (Synthesis, 2023)
Terminal alkynes undergo intermolecular hydroaminoalkylation reactions with secondary amines in the presence of titanium catalysts and depending on the catalyst and the structure of the substrates, allylic amines and/or imines are formed as products in moderate yields. In addition, the desired allylamines can also be obtained from a convenient reaction sequence consisting of an initial hydroaminoalkylation of trimethylsilyl-protected alkynes and a subsequent protodesilylation that selectively delivers γ-unsubstituted allylamines.
Keywords: alkynes; allylamines; C–H activation; hydroaminoalkylation; titanium; catalysis